2019
DOI: 10.1097/brs.0000000000002781
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Cross-Cultural Adaptation, Reliability, and Validity of the Persian Versions of the Copenhagen Neck Function Disability Scale and Neck Bournemouth Questionnaire

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 33 publications
3
17
1
Order By: Relevance
“…26 In addition, based on the exploratory factor analysis, we also tested the one-dimensional structure of the Neck Bournemouth Questionnaire, as well as the study carried out with the Persian version. 24 In all versions tested and compared to the present study, we found unacceptable values for the root mean square error of approximation and chi-square/ degree of freedom.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…26 In addition, based on the exploratory factor analysis, we also tested the one-dimensional structure of the Neck Bournemouth Questionnaire, as well as the study carried out with the Persian version. 24 In all versions tested and compared to the present study, we found unacceptable values for the root mean square error of approximation and chi-square/ degree of freedom.…”
Section: Discussioncontrasting
confidence: 43%
“…From this, we compare here four Neck Bournemouth Questionnaire structures (Table 2): structure with one domain and seven items (items 1-7), here called Model 1, as suggested by exploratory factor analysis and the study conducted by Ghasemi et al 24 ; structure with two domains and seven items (domain 1 = items 1, 2, 3, 6, and 7; domain 2 = items 4 and 5), here called Model 2, as suggested by the study of Geri et al 25 ; structure with two domains and six items (domain 1 = items 1, 2, 3, and 6; domain 2 = items 4 and 5), here called Model 3, as suggested by the study of Geri et al 25 ; and structure with two domains and six items (domain 1 = items 2, 3, 6, and 7; domain 2 = items 4 and 5), here called Model 4, as suggested by the study of Özel Asliyüce et al 26 We observed that Models 1, 2, 3, and 4 presented a high amount of residues, identified by the value of root mean square error of approximation > 0.08 and chi-square/degree of freedom > 3.00. In addition, Model 1 has inadequate values for the Tucker-Lewis Index and standardized root mean square residual.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If an item from the questionnaire receives a score equal to or greater than 0.79, it is approved (21). Construct validity: Construct validity of the scale was evaluated by exploratory factor analysis using principal component analysis and varimax rotation (22). The eigenvalues greater than one were considered as having a significant contribution in explaining the overall model variation.…”
Section: Validity Face Validitymentioning
confidence: 99%